Liver herniation mimicking a thoracic tumor with restoration of the liver surface structure on closure of the hernia orifice under thoracoscopic surgery. Issue 4 (20th April 2022) - Ikeda, Takeshi; Sumiya, Ryusuke; Sugimura, Aya; Hirai, Hoshie; Nagasaka, Satoshi
Abstract: Non‐congenital, non‐traumatic spontaneous diaphragmatic liver hernia in adults is extremely rare and sometimes misdiagnosed as a thoracic tumor. Almost all previous reports with a definitive diagnosis reported preservation; thus, differential diagnosis is extremely important for planning optimal management of such clinical conditions. An abnormal shadow in the right lower lung field was detected on chest radiography in a 61‐year‐old woman. Further imaging study revealed a 33‐mm diameter mass adjacent to the right diaphragm. Thoracoscopic surgery was performed as diagnostic treatment. We found a pale hemispherical herniated liver on the central tendon of the diaphragm. After repositioning the herniated liver, the orifice was closed with a non‐absorbable suture, and the surface of the liver returned to being a perfectly smooth surface. With this result, we believe that repair of diaphragmatic liver hernia through a minimally invasive procedure has great benefits for patients.